Real-time brain computer interface (BCI) for robotic systems - Seng, Deon Wee How (2017)
Research and development in computer technology has been intense and successful since the early 20th century till today. It has allowed us to possess most of our prized possession today, such as our smartphones and computers. Today, technology is ubiquitous with an ever-growing demand for better technology. Not only does it improve and changes our daily life, computer technology has also contributed greatly to assist in medical operations.